Galanin 3 receptor‐deficient mice show no alteration in the oxazolone‐induced contact dermatitis phenotype. Issue 9 (13th July 2016) - Botz, Bálint; Brunner, Susanne M.; Kemény, Ágnes; Pintér, Erika; McDougall, Jason J.; Kofler, Barbara; Helyes, Zsuzsanna
Abstract: Allergic contact dermatitis (ACD) is an inflammatory skin disease induced by allergen exposure and characterized by erythema, oedema and immune cell infiltration. The sensory peptide galanin (GAL) and its three receptors (GAL1–3 ) are involved in regulating inflammation. As GAL and its receptors are expressed in human and murine skin and GAL expression is increased in oxazolone‐induced contact allergy, it could play a role in dermatitis. As GAL reduces neurogenic plasma extravasation in the mouse skin via GAL3 activation, the role of GAL3 in the oxazolone‐induced dermatitis model was explored. Following topical challenge with oxazolone, GAL 3 gene‐deficient mice showed a trend towards reduced ear thickness. Plasma extravasation and neutrophil infiltration increased considerably upon oxazolone challenge in both GAL3 knockout animals and wild‐type controls without any observable effect of the gene deletion. We conclude that a lack of GAL3 does not influence oxazolone‐induced ACD.